Analisis Yuridis Putusan Perkara No. 36/Pdt.G/2023/PN Pdg Tentang Gugatan Parate Executie Hak Tanggungan Atas Dasar Wanprestasi Terhadap Debitur - Maridus Maridus; Darwan Suryadi (Normative Jurnal Ilmiah Hukum, 2026)
Banking is one of the economic sectors that is vital for economic growth, but banking is often faced with financial risks caused by high non-performing loans. In case Number: 36/Pdt.G/2023/PN Pdg explains that the creditor will conduct an auction of the Mortgage Right object to guarantee debt repayment. The problem started when the plaintiff neglected to fulfill his credit collectibility obligations, classified as a "bad" credit (collectibility 5). Defendant I has sent 3 (three) warning letters, but the Plaintiff still has not fulfilled his obligations. Defendant I stated that the Plaintiff has defaulted and will execute the collateral. The research method used in this research is normative juridical, namely an approach carried out by studying statutory regulations. The results of this study indicate that the Padang District Court's decision which rejected the Plaintiff's lawsuit shows that the creditor's right to carry out Parate Execution of collateral if the debtor is in default is protected by law. The rejection of the parate execution lawsuit indicates that the creditor's execution was deemed valid and in accordance with Article 6 of Law Number 4 of 1996. The party declared the loser in Decision Number 36/Pdt.G/2023/PN Pdg is advised to exercise caution in making agreements and to comply with agreed rights and obligations without sacrificing legal certainty.